Avaliação de alternativas para suprimento de água para consumo humano na região semi-arida de Minas Gerais - Alberto Simon Schvartzman (2007)
The present research had as its main objective the assessment of the water resourcesmanagement in the semiarid region of the State of Minas Gerais, verifying the feasibility ofthe adoption of conventional water supply and roof water harvesting techniques in order tosatisfy the needs of human consumption. The Jequitinhonha river basin was selected for thedevelopment of the study. In the methodology technical, economical, social andadministration, operation and maintenance criteria were settled to evaluate the domestic watersystems. To assess the domestic roof water harvesting alternative technique, in which cisternsare used to collect the rainwater that reaches the houses roofs, a model was developed andwas applied utilizing daily rainfall data from two monitoring stations in the Jequitinhonhariver basin. The results lead to alternative choices that could satisfy the water humanconsumption of people in the semiarid region of the State of Minas Gerais, especially thedispersed communities and isolated families, with a regular attention from water resourcesand sanitation policies. Moreover the feasibility studies show that there are some conditionsthat have to be observed before the implementation of the best alternative, such as availableprograms, projects and financial resources, to assist the public decisions. Some discussionsshowed after the evaluations and studies, which were performed at the selected river basin,stand out about the effectiveness of water resources management in the State of Minas Gerais,the overlapping of the policies related to water resources and the non governmentalorganizations cisterns building actions. The research stands out the necessity of more studiesabout sustainable administration, operation and maintenance of domestic water supplysystems and about the optimization on implementation costs. Finally it is concluded that thewater scarcity in the semiarid region of the State of Minas Gerais could be related to the nonutilizationof existing superficial and groundwater resources. It is also concluded that there isa need of a better integration among the public policies as to permit the elaboration of astrategic plan for that region. It is recommended the complementation of legislation on waterresources and basic sanitation with the incorporation of water harvesting techniques, witheconomic and financial incentives for their implementation.